The meme-ification of black identity: tracing stereotypes from Southern literature to the digital age - Poleac, Gabriela; Colibaba, Adriana Ioana Giorgiana (Technium Social Sciences Journal, 2025)
From its literary roots in Southern American narratives to their rearticulation in modern meme culture, this paper explores the persistence and evolution of African-American stereotypes. The study begins with a critical analysis of Southern literature from the 19th and early 20th centuries, highlighting the historical construction of Black identity through reductive tropes. The article then examines how meme culture, through irony, remix, and repetition, functions as a site of resistance and a tool of stereotype amplification, building on ideas of digital culture and media virality. The analysis shows how humour, affect, and platform logics can re-inscribe historically sensitive imagery under the pretence of entertainment by using a collection of viral memes that contain African-American characters or tropes. The article concludes by considering the current ramifications of this meme-ification process, including its impact on racial social discourse, cultural identity, and public perception. The meme economy frequently maintains a feedback cycle that normalises and propagates racialised tropes in novel, digitally mediated ways, regardless of acts of rebellion.